The horror at Camp Jellyjam - Stine, R. L. (New York : Scholastic, 2009)
During a stay at King Jellyjam's Sports Camp, Wendy thinks the counselors are a little too happy--eerily happy--and concerned about winning, but her "sports freak" brother is not convinced.
"Now with bonus features!"--Cover.
3.7
5-8
Keywords: Brothers and sisters -- Juvenile fiction; Sports camps -- Juvenile fiction; Brothers and sisters -- Fiction; Camps -- Fiction; Horror stories; Camps -- Fiction; Horror fiction; Siblings -- Fiction; Horror fiction